Analysis of blood flow in 3d heart valve model under steady state condition - Mohammad Iskandar, Othman (2012)
Mitral valve (MV) and Aortic valve (AV) are very important in circulatory blood inside the heart which function as a gate for the blood flow. Since the heart valves not working properly, the normal flow of blood inside the heart will be interrupeted. Malfunctioning Mitral Valve and Aortic Valve will cause death if it not immediately detected. The aims of this study are to investigate the blood flow pattern for MV and AV in 3D view which developed by ADINA-FSI application. All the parameter of blood obtained from the previous studies. Both of valve models have been implemented without ventricles and presented as a Newtonian fluid flow in steady condition. The simulation from this study will cover the blood flow pattern in term of velocity, effective stress on the leaflets, strain occurred in the critical area of both heart valves and the nodal pressure pattern flow during the systolic process phase. Moreover, these studies enable to investigate performance characteristics such as effective stress and strain which are very difficult to evaluate experimentally. The findings showed, the velocity and nodal pressure are linear correlation with the blood pressure increased during systole process. Effective stress and strain results showed the critical area region and maximum values with fix Young Modulus 2MPa. The significant simulation results from this study were very useful to give a clear view to the medical practitioners about the pattern of blood flow through MV and AV. Furthermore, these models can be used to investigate heart valve failure and subsequent surgical repair treatment.